Tax guide for short-term rentals : Airbnb, HomeAway, VRBO & more - Fishman, Stephen (Nolo, 2018)
"As a short-term rental host, you're entitled to many valuable deductions and other tax benefits. This book--the first of its kind--shows you how to pay no more tax than necessary on your rental income while complying with IRS rules. Learn everything you need to know about taxes, including: what deductions you should be taking, how to report your short-term rental income, how to deduct losses, vacation home and tax-free rental rules, how to allocate costs when you rent a room in your home, and how to keep proper records. Whether you rent your property through Airbnb, FlipKey, HomeAway, TripAdvisor, Craigslist, or VRBO, you want to make sure you understand these tax rules. That way, you can rest assured you are making the most out of your hosting business without risking problems with the IRS"--Amazon.com.